Investigating The Predictive Effect Of Offence-Specific Forgiveness And Assessing Attributions In Marriage On Marital Satisfaction - Mehmet Engin DENİZ; Gülgün UZUN; Hacer YILDIRIM KURTULUŞ (Elementary Education Online, 2023)
The aim of this study is to examine the relationship between marital satisfaction and offencespecific forgiveness and assessing attributions in marriage and to investigate the predictive effect of offence-specific forgiveness and assessing attributions in marriage on marital satisfaction. The sample of this research consists of 160 married women and 30 married men living in İstanbul. The data of the study were collected with the help of 3 scale. These are The Marital Offence-Specific Forgiveness Scale, Marital Satisfaction Scale , Assessing Attributions in Marriage Scale. According to research findings, there is a significant negative correlation between marital satisfaction and the Marital offence-specific forgiveness in marriage (distinct correlated dimensions Resentment-Avoidance) and also Resentment-Avoidance of the Marital offence-specific forgiveness in marriage predicts marriage satisfaction. Another result is that there is a negative relationship between marital satisfaction and assessing attributions in marriage. Assessing attributions in marriage is a significant predictor of marriage satisfaction.